2014
DOI: 10.3171/2013.12.spine12629
|View full text |Cite
|
Sign up to set email alerts
|

Extraforaminal compression of the L-5 nerve root at the lumbosacral junction: clinical analysis, decompression technique, and outcome

Abstract: Object Extraforaminal compression of the L-5 nerve encompasses multiple pathological entities and may result from disc herniations as well as bony (osteophytes or sacral ala) or ligamentous (sacroiliac ligament and lumbosacral band) compression. Several other factors, such as disc space collapse or coronal wedging, can also contribute to narrowing of the extraforaminal space. The extraforaminal space at L5–S1 has unique anatomical features compared with the upper lumbar levels, which makes surgical access to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 33 publications
2
29
0
6
Order By: Relevance
“…Good to excellent outcomes in nearly 90% of FDH have been shown with the MIS endoscopic technique in the 11 patients described by Foley et al [18] Equally good results have been shown in subsequent reports with the MIS technique for FDH as well as degenerative foraminal stenosis [5,16,23]. Perlier et al [23] described the MIS approach in 46 patients with results comparable to ours and without complications.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Good to excellent outcomes in nearly 90% of FDH have been shown with the MIS endoscopic technique in the 11 patients described by Foley et al [18] Equally good results have been shown in subsequent reports with the MIS technique for FDH as well as degenerative foraminal stenosis [5,16,23]. Perlier et al [23] described the MIS approach in 46 patients with results comparable to ours and without complications.…”
Section: Discussionsupporting
confidence: 59%
“…Their average hospitalization was 3 days compared to our 1 ± 1 days. Lee et al [5] used the MIS technique in 52 patients with L5-S1 foraminal disc herniations only. The results were as good as those described above, also without complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As being reported before, degenerative change such as facet hypertrophy can appear at the adjacent level following spinal fusion (4,5). Foraminal stenosis can also occur due to facet hypertrophy (4, 5) and disc collapse (22). Orita et al (6) reported a series of patients with foraminal stenosis at the adjacent level following spinal fusion in whom symptoms appeared on average 13.3 months after surgery.…”
Section: Discussionmentioning
confidence: 87%